Experimental and Numerical Analysis of Thermal and Thermomechanical Behavior of a Power Inductor Accompanied by a Reliability Study - Bendaou, Om; Gautrelet, C; Elhami, A; Agouzoul, M (IOP conference series. Materials Science and Engineering, 2017)
In practice, when feeding the electrical and electronic components, they generate heat by Joule's effect, which will cause an increase in temperature and provoking mechanical deformations related to the expansion of the materials. It is therefore this aspect that is the subject of our study on the thermal and thermomechanical characterization of a ferrite power inductor by experimental and numerical channels. For this purpose, a finite element model was developed and calibrated by comparing its results to the experimental results obtained via thermal measurements and measurements by speckle interferometry system. A reliability analysis on the power inductor was performed numerically, based on the coupling between finite element model validated and the methods of Monte Carlo, FORM and SORM.